The quality of the shrimp head meal fermented using Bacillus sp. PAS7 isolates at different dosages of inoculum as fish feedstuff. Issue 1 (July 2020) - Mulyasari,; Samsudin, R; Makatutu, D
Abstract: Shrimp head is a feedstuff that potential to be developed as an alternative source of protein to substitute fish meal. It is because the shrimp head contains a high protein and its availability in Indonesia is quite abundant. However, this protein can not be utilized by fish because it contains high crude fiber (chitin) and ash which is difficult to digest. This study aimed to improve the quality of shrimp head meal by fermentation using Bacillus sp PAS7 at different inoculum doses and evaluate its nutrient content. The study was conducted in a completely randomized design (CRD) of four treatments and three replications. The treatment was carried out by varying concentrations of 0, 3, 5 and 7% per gram (weight) of shrimp head meal (v / w). Fermentation was done for three days at 28°C. The parameters measured were reducing sugar, soluble protein and proximate analysis (crude protein, crude fiber, ash and crude fat). The results showed that all dosage treatments had crude protein, soluble protein and crude fiber, which were better than control. Where dose of 7% had the highest soluble protein content (6.25 mg mL −1 ) and the lowest crude fiber content (15.02%) compared to other treatments.